Improvement of in Vitro somatic embryogenesis in Cashew (Anacardium occidentale L.) - Rekha S (Department of Horticulture, College of Agriculture, 1999)
Studies were conducted for improving techniques for in vitro somatic embryogenesis in cashew during 1996-1999 in the Plant Tissue Culture Laboratory of the Department of Horticulture, College of Agriculture, Vellayani. Attempts were made to standardise the various stages of somatic embryogenesis, namely, induction, initiation, maturation and germination using nucellus and embryo mass as explants. Out of the two explants tried, nucellus responded better than embryo mass in initiating embryogenic callus/somatic embryoids. Induction of somatic embryogenesis from nucellus was found to occur at its maximum when cultured in darkness on MS basal medium having half strength major salts, supplemented with 2,4-D 1.0 mg/l, BA 1.0 mg/l, NAA 1.0 mg/l, sucrose 30.0 g/l, Activated charcoal 0.5 g/l and agar 6.0 g/l. The best treatment identified for the induction of embryogenic callus / somatic embryoids from embryo mass was MS basal medium supplemented with 2,4-D 4.0 mg/l, NAA 4.0 mg/l, kinetin 4.0 mg/l, adenine sulphate 40.0 mg/l, yeast extract 200.0 mg/l, PVP 250.0 mg/l, sucrose 30.0 g/l and agar 5.5 g/l, in dark culture condition at regulated temperature (26 ± 2°C).